Nauczanie i rozwijanie sprawności komunikacyjnych w obcojęzycznym dyskursie specjalistycznym. Potrzeby, wyzywania, innowacje - Kubica, Małgorzata (Neofilolog, 2010)
This paper concerns the teaching of languages for specific purposes to adults. It shows the growing need for this kind of teaching from the European and multicultural perspective. Specialist discourse compared to teaching general language will be described and the implications of such a comparison will analyzed. The paper emphasizes the necessity of determining learners’ needs in specialist communication and the use of such educational innovations as the Internet and the language action perspective.